CONTENT AND LANGUAGE ANALYSIS â€œTHINK GLOBALLY ACT LOCALLYâ€ FOR JUNIOR HIGH SCHOOL PUBLISHED BY MINISTRY OF EDUCATION AND CULTURE OF INDONESIA - Aristiawan, Danul; Herman, Herman (Yavana Bhasha : Journal of English Language Education, 2021)
Textbook is one of the learning materials that can be used by teacher and students in order to help the teaching and learning process in the classroom. An analysis to a textbook is needed, moreover after the curriculum was launched. The object of the study is students English textbook entitled â€œ Think globally act locallyâ€ published by Ministry of Education and Culture of the Republic of Indonesia. This study was designed in descriptive qualitative research because the object of the study was a document book. Moreover, as the data was in the form of words and documents, so the data were analyzed qualitatively. The results of the study show that the suitability of the material in the textbook is 78.12%, which can be concluded that the material from the textbook has met the standard of content eligibility in the textbook. Meanwhile, the feasibility of using the language in the textbook is 75%, which can be concluded that the book uses language in accordance with BSNP assessment standards